Kearifan Lingkungan dalam Puisi Anak Dongeng Pohon Pisang Karya Achmad Sultoni - Anantama, Muharsyam Dwi; Suyanto, Edi; Prayogi, Rahmat (Edukasi Lingua Sastra, 2024)
As a cultural product, literary works are related to the environment in which they are born. One of the things meant is related to ecological issues. Poetry as part of literary works can reflect ecological problems. This study aims to explore ecological elements in the poetry collection Dongeng Pohon Pisang by Achmad Sultoni. The form of this research is qualitative descriptive with a literary ecology approach. The poetry collection Dongeng Pohon Pisang by Achmad Sultoni is the source of data in this study. Words, sentences, and phrases in the poetry collection Dongeng Pohon Pisang by Achmad Sultoni that contain ecological elements are the data in this study. To obtain data, this study uses data collection techniques in the form of document or library studies. The data that has been obtained is then analyzed using an interactive analysis model. The results of this study indicate that the poetry collection Dongeng Pohon Pisang by Achmad Sultoni is very thick with ecological nuances and themes. The ecological nuance is reinforced by the ecocentrism attitude presented by the author.